Engineering Materials Informatics - Cebon, D.; Ashby, M.F. (MRS bulletin, 2006)
This article discusses the need for materials data and materials data management software during product development. Key issues are the changing materials data needs (from general to specific) as the design process proceeds, as well as the requirements for software systems that can automate the key data management tasks: capture, analysis, deployment, and maintenance. Specific issues requiring attention are flexibility of data management, change control, version control, quality control, and traceability of information.